2019
DOI: 10.20344/amp.10892
|View full text |Cite
|
Sign up to set email alerts
|

Portal Venous Pressure Variation during Hepatectomy: A Prospective Study

Abstract: Introduction: Excessive portal venous pressure in the liver remnant is an independent factor in the occurrence of posthepatectomy liver failure and small-for-size syndrome. The baseline portal pressure prior to hepatectomy was not considered previously. The aim of this study is to assess the impact of portal pressure change during hepatectomy on the patient outcome.Material and Methods: Prospective observational study including 30 patients subjected to intraoperative measurement of portal pressure before and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(23 citation statements)
references
References 21 publications
0
23
0
Order By: Relevance
“…See Table 2. Following the original literature search 10 studies (with 712 patients) from a pool of 68 studies were selected [6][7][8][9][10][11][12][13][14][15] [Fig. 1].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…See Table 2. Following the original literature search 10 studies (with 712 patients) from a pool of 68 studies were selected [6][7][8][9][10][11][12][13][14][15] [Fig. 1].…”
Section: Resultsmentioning
confidence: 99%
“…Three prospective studies and two RCTs were excluded for not having recorded postresection direct PVP measurement [26][27][28][29][30] Only two studies reported the Future Liver Remnant volumes. 13,14 Pre-and post-resection PVP The definition of elevated PVP, results of PVP and definitions and relationship of PVP to outcomes evaluated are shown in Tables 3 and 4. The overall median (range) baseline PVP was 11.4 mmHg (7.3-16.4) with 50% of patients with cirrhosis.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations